PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID UNTUK PEMBELAJARAN BAHASA ARAB MATERI ISIM DHOMIR - Yogaraksa, Muamar; Erlina, Erlina; Ghazi, Fachrul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to develop Android-based learning media for Arabic language learning, specifically on the topic of Isim Dhomir. The media was developed using the Hannafin and Peck model, consisting of three stages: needs analysis, design, and development. The study was conducted at MTs Muhammadiyah Sukarame, involving 8th-grade students as participants. Validation by experts indicated that the media is highly feasible, with an average score of 92%. Teachers and students provided very positive responses, with averages of 87% for students and 89% for teachers. The use of this media improved student learning outcomes, as evidenced by the average pre-test score of 68, which increased to 85 in the post-test, achieving a gain percentage of 53%. This study demonstrates that Android-based media effectively enhance student motivation and understanding in Arabic language learning.